Pengaruh Stres Kerja dan Beban Kerja Terhadap Kinerja Karyawan di CV. Kurnia Laut Biru Kabupaten Jombang - Hanum Dwi Saputriningsih; Hartono Hartono; Agoes Hadi Poernomo (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to analyze the effect of work stress and workload on employee performance at CV. Kurnia Laut Biru. This type of research is quantitative. The population studied was all employees of CV. Kurnia Laut Biru, Jombang Regency, totaling 35 employees. The sampling technique used saturated sampling, which means that all members of the population were sampled. Data collection was carried out by distributing questionnaires, and then analyzed using multiple linear regression with the help of the SPSS version 29 program. The hypothesis testing used was the partial significance test (t-test) and the simultaneous significance test (f-test). The results of the study concluded that: work stress has a significant negative effect on employee performance at CV. Kurnia Laut Biru, Jombang Regency, workload has a significant negative effect on employee performance at CV. Kurnia Laut Biru, Jombang Regency, And together, work stress and workload significantly affect employee performance at CV. Kurnia Laut Biru, Jombang Regency.